THE EFFECTIVENESS OF VISUAL MEDIA IN INCREASING SELF-DEVELOPMENT ABILITY TOWARD CHILDREN WITH MILD MENTAL RETARDATION - Gardiana Karya; Mohammad Efendi; Ediyanto Ediyanto; Asep Sunandar (Jurnal Pendidikan Humaniora, 2021)
Abstract: This research aims to prove the effectiveness of visual media to improve self-development skills in children with mild visual impairment. The ability to do self-development is still low, so training requires a structured defense approach with visual media in picture cards. The research method used in this study is a class action. The class-action study intended by researchers is a group of children in the guesthouse Bhakti Luhur Malang Foundation in 4 children who have a mild visual impairment. The purpose of this study is the improvement and change in achieving more optimal results. The results showed an increase in scores. In the first cycle, the performance test results scored 62.5% and observation results of 60.2%. In the second cycle, the child's ability to inside by achieving a score of 77.7% and observation results of 79 %. Thus, it shows that a structured learning approach with visual media can increase self-development in lightly visually impaired children. Keywords: structured learning approach, visual media, self-development skills, lightly visually impaired children Abstrak: Penelitian ini bertujuan untuk membuktikan efektivitas media visual dalam meningkatkan keterampilan pengembangan diri pada anak tunanetra ringan. Kemampuan dalam melakukan pengembangan diri masih rendah, sehingga pelatihan memerlukan pendekatan pertahanan terstruktur dengan media visual dalam kartu bergambar. Metode penelitian yang digunakan dalam penelitian ini adalah tindakan kelas. Penelitian tindakan kelas yang dimaksud peneliti adalah sekelompok anak di Wisma Yayasan Bhakti Luhur Malang pada 4 anak yang memiliki gangguan penglihatan ringan. Tujuan dari penelitian ini adalah perbaikan dan perubahan dalam mencapai hasil yang lebih optimal. Hasilnya menunjukkan peningkatan skor. Pada siklus I, hasil tes kinerja mendapat skor 62,5% dan hasil observasi 60,2%. Pada siklus II kemampuan anak dalam dengan mencapai skor 77,7% dan hasil observasi 79%. Dengan demikian menunjukkan bahwa pendekatan pembelajaran terstruktur dengan media visual dapat meningkatkan pengembangan diri pada anak tunanetra ringan.Kata kunci: pendekatan pembelajaran terstruktur, media visual, keterampilan pengembangan diri, anak tunanetra ringan